Fluxos de informação que subsidiam o processo de inteligência competitiva - Valentim, Marta Lígia Pomim [UNESP]; Souza, Juliete Susann Ferreira de [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2013)
Information flows are responsible for the dynamics and the interaction between the various sectors of the organization and among individuals who work in it. By mapping performed in internal and external environments of the organization, it is possible to highlight the informational needs of organizational individual, since they depend on data, information and knowledge to perform their actions in the corporate environment. To meet the information needs of organizational individual need to manage the existing information flows, how it can settle and move effectively in the organizational environment. It is argued that the environments and existing information flows in an organization, subsidize the process of organizational competitive intelligence, since they are inputs for decision making and enable the planning and execution of actions in the short, medium and long term.

Os fluxos de informação são responsáveis pela dinâmica e pela interação entre os diversos setores da organização e entre os indivíduos que nela atuam. Por meio do mapeamento realizado nos ambientes internos e externos da organização, é possível evidenciar as necessidades informacionais dos sujeitos organizacionais, uma vez que dependem de dados, informação e conhecimento para desempenhar suas ações no ambiente corporativo. Para atender as necessidades de informação dos sujeitos organizacionais é preciso gerenciar os fluxos informacionais existentes, de que forma se possam se estabelecer e transitar eficientemente no ambiente organizacional. Defende-se que os ambientes e os fluxos informacionais existentes em uma organização, subsidiam o processo de inteligência competitiva organizacional, uma vez que são insumos para a tomada de decisão e possibilitam o planejamento e execução de ações de curto, médio e longo prazo.
Keywords: Fluxos de Informação; Gestão da Informação; Gestão do Conhecimento; Processo Decisório; Inteligência Competitiva; Ambientes Informacionais